Dental aspects of purging bulimia - Manevski Jovana; Stojšin Ivana; Vukoje Karolina; Janković Ognjenka (Vojnosanitetski Pregled)
vomiting, which in long term can result in irreversible loss of dental tissue, most commonly manifested as dental erosion. Frequent purging, xerostomia, lack of oral hygiene and acidic environment are also suitable for caries development. The aim of the research was to determine the presence, localization and degree of dental erosion using Basic Erosive Wear Examination (BEWE) index system, as well as to determine the Decayed, Missing and Filled Teeth (DMFT) index in purging bulimic patients. Methods. The study involved 30 purging bulimic patients and 30 healthy subjects. Used methods were survey (questionnaire) and clinical examination. The clinical examination included intraoral inspection and assessment of dental status using BEWE and DMFT index. Results. On the bases of conducted research, it has been found that dental erosion are significantly more often present in purging bulimics compared to the controls (χ2 = 5.963, p < 0.05), that eroded lesions are more severe in the bulimic group (t = 3.925, p < 0.05) and predominantly located on oral surfaces of the teeth (χ2 = 10.561, p < 0.05). DMFT index values showed no significant difference between bulimic patients and controls (t = 0.741, p = 0.461). Conclusion. Dental erosion are often encountered in patients suffering purging bulimia, especially on oral surfaces of anterior teeth that come into direct contact with gastric acid, so many bulimics exhibit high values of erosive tooth wear on mentioned surfaces. DMFT index score did not show significant differences compared to healthy participants, but due to complexity of carious process further investigation is necessary.